PLANT PATHOLOGY IN MEXICO - STAKMAN, EC; HARRAR, JG; GONZALEZ FRANEO, JOSE (Laboratorio de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1973)
R meliloti bacteriophage was isolated from Mexican soils by the method of Fuller and Vandecaveye, with a modification in the culture medium and the filtration device, and tested against strains of R meliloti, R phaseoli, R trijolii, and R japonicum
Keywords: PLANT PATHOLOGY, MEXICO; MULTIDISCIPLINARIA; BIOLOGIA VEGETAL; BOTANICA GENERAL